2019
DOI: 10.21276/ijcmr.2019.6.9.25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Bullying Victimization among in-School Adolescents in Sokoto Metropolis, North-Western Nigeria

Abstract: Introduction: Bullying victimization is a common experience among adolescents. Victimization is associated with negative consequences including negative mental outcomes, poor academic results, and poor social relationships. We describe the various forms of bullying victimization and the predictors of victimization among in-school adolescents in Sokoto metropolis. Material and Methods:We conducted a cross-sectional study among in-school adolescents in Sokoto metropolis. Using a multistage sampling technique, 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…This finding is consistent with previous work conducted in Nigeria and other low-and-middle-income countries. 12 , 15 , 28 , 30 , 34 , 35 , 50 Another common type of bullying experienced in this study was verbal bullying, such as hurtful name-calling or making fun of tribes or families, followed by relational bullying, such as being ignored or spreading rumors, then cyberbullying. In contrast to physical bullying, verbal bullying was reported to be more common in some studies.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This finding is consistent with previous work conducted in Nigeria and other low-and-middle-income countries. 12 , 15 , 28 , 30 , 34 , 35 , 50 Another common type of bullying experienced in this study was verbal bullying, such as hurtful name-calling or making fun of tribes or families, followed by relational bullying, such as being ignored or spreading rumors, then cyberbullying. In contrast to physical bullying, verbal bullying was reported to be more common in some studies.…”
Section: Discussionmentioning
confidence: 89%
“… 21 , 24 , 48 Furthermore, the prevalence of bullying in this study was comparable to studies reported in Osun (50%), Ondo (27.5%), and Oyo (47.9%), 28 , 35 , 49 but was relatively low compared to studies conducted in Benin City (80%), Sokoto (65%), and Port Harcourt (82.2%) states in Nigeria. 27 , 30 , 32 Physical bullying was the most common type in this population because this is seen as either a sign of older students demanding respect from younger ones or the intimidation of peers to instill fear. Furthermore, children experience some sort of bullying from home as a sign of correction from parents or from school as corporal punishment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobacco smoking is associated with an extensive list of health disorders as well as reduction of life expectancy (Raji et al, 2013). Smoking can make it harder for a woman to become pregnant.…”
Section: Introductionmentioning
confidence: 99%